Optimization Design of Fresh Cold Chain Logistics Network for Carbon Footprint - Bao, Tingting; Yu, Jiaxuan; Chen, Kai; Zhang, Xumei; Chen, Chen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
With the upgrading of consumption, the public demand for cold chain products and quality requirements is getting higher and higher, which promotes the rapid development of China’s cold chain logistics industry. As a transportation business with high energy consumption and high carbon emissions, cold chain logistics makes enterprises face high-cost pressure. Also, it contradicts the current low-carbon economy advocated by society. In order to balance the economic benefits brought by the rapid development of cold chain logistics and the negative impact on the environment, this paper constructs a multi-objective model with the lowest network construction cost and carbon emission as the objective function based on the customer demand in the region and designs a genetic algorithm with local search to solve the model. Simultaneously optimizing the distribution center location and distribution plan, the construction cost and carbon emission of the cold chain logistics network can be reduced to save costs and improve economic benefits. At the same time, the economic and social benefits are taken into account, which can provide a scientific decision-making basis for the network construction and operation of enterprises with cold chain logistics demands and contribute to the sustainable development of cold chain logistics.